2012
DOI: 10.1007/s10557-012-6373-5
|View full text |Cite
|
Sign up to set email alerts
|

ApoA-I Induction as a Potential Cardioprotective Strategy: Rationale for the SUSTAIN and ASSURE Studies

Abstract: ApoA-I induction represents a potential novel strategy to reduce cardiovascular risk, by generating nascent HDL particles. These studies will provide early evaluation of the effects of RVX-208 on lipids and atherosclerotic plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 46 publications
(48 reference statements)
1
47
0
2
Order By: Relevance
“…1A) has been developed by Resverlogix Corporation for the treatment of cardiovascular diseases associated with atherosclerosis (27,28) and has more recently entered clinical studies on Alzheimer's disease (29). RVX-208 is a derivative of the plant polyphenol resveratrol (3,4',5-trihydroxy-transstilbene) that leads to an increase of plasma levels of the high-density lipid protein ApoA1.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A) has been developed by Resverlogix Corporation for the treatment of cardiovascular diseases associated with atherosclerosis (27,28) and has more recently entered clinical studies on Alzheimer's disease (29). RVX-208 is a derivative of the plant polyphenol resveratrol (3,4',5-trihydroxy-transstilbene) that leads to an increase of plasma levels of the high-density lipid protein ApoA1.…”
mentioning
confidence: 99%
“…RVX-208 is a derivative of the plant polyphenol resveratrol (3,4',5-trihydroxy-transstilbene) that leads to an increase of plasma levels of the high-density lipid protein ApoA1. Increasing ApoA1 levels has emerged as a promising approach for the treatment of atherosclerosis (30), and recent phase IIb clinical trial data using RVX-208 as an ApoA1 modulator have been encouraging (28). ApoA1 expression is regulated by BET proteins, and chemical inhibition of BET bromodomains has been associated with ApoA1 up-regulation on transcriptional and protein levels (9,31,32).…”
mentioning
confidence: 99%
“…The ASSURE (ApoAI Synthesis Stimulation and Intravascular Ultrasound for Coronary Atheroma Regression Evaluation) trial examined the effect of 26 weeks of treatment with RVX-208 on the progression of coronary atherosclerosis as assessed by intravascular ultrasound (IVUS) in 323 subjects with symptomatic CAD and low HDL-C levels. 44 No significant change in plaque regression was observed between placebo and the RVX-208 group. Furthermore, the drug did not increase apoAI or HDL-C levels, but it induced transaminase elevations.…”
Section: Hdl Therapiesmentioning
confidence: 90%
“…It is of note that the transaminase increase in the ASSERT trial was primarily observed in simvastatin-treated patients, and patients on simvastatin will therefore be excluded from the other phase IIb studies. 69 On June 27, 2013, Resverlogix reported that the ASSURE trial did not meet its primary end point of −0.6% atheroma volume regression. The RVX-208-treated group had −0.4% regression in atheroma volume (P=0.08).…”
Section: Apoa-1 Inductionmentioning
confidence: 99%